A Stochastic Weakly Damped, Forced KdV-BO Equation - Guolian Wang (Abstract and Applied Analysis)
We investigate the long time behavior of the damped, forced KdV-BO equation driven by white noise. We first show that the global solution generates a random dynamical system. By energy type estimates and dispersive properties, we then prove that this system possesses a weak random attractor in the space H1(ℝ).